Re: Easy simplification with Mathematica?
- To: mathgroup at smc.vnet.net
- Subject: [mg111163] Re: Easy simplification with Mathematica?
- From: Bob Hanlon <hanlonr at cox.net>
- Date: Thu, 22 Jul 2010 05:43:46 -0400 (EDT)
expr1 = a + b - 2*c; subs1 = {t1 == a - c, t2 == b - c}; expr2 = HoldForm[Evaluate[ Simplify[expr1, subs1]]] /. (Rule @@@ subs1) (a-c)+(b-c) expr1 == expr2 // ReleaseHold True expr3 = a*b + a*c - 2*a*d + b*c - 2*b*d - 2*c*d + 3*d^2; subs2 = Thread[{t1, t2, t3} == {a, b, c} - d] {t1 == a - d, t2 == b - d, t3 == c - d} expr4 = HoldForm[Evaluate[ Simplify[expr3, subs2]]] /. (Rule @@@ subs2) (b-d) (c-d)+(a-d) ((b-d)+(c-d)) expr3 == expr4 // ReleaseHold // Simplify True Bob Hanlon ---- fajar <fajar96te at yahoo.com> wrote: ============= Hi all, I'm new to symbolic computation. I have this coming from previous computation: a + b -2*c How can I convert that expression, with Mathematica, into: (a - c) + (b - c) ? Another example: Given a*b + a*c - 2*a*d + b*c - 2*b*d - 2*c*d + 3*d^2 How can I convert that expression, with Mathematica, into: (a-d)*(b-d) + (a-d)*(c-d) + (b-d)*(c-d) ? Thanks Fajar